Implicações do perfil epidemiológico do servidor da Universidade Federal de Goiás para as ações educativas - Oliveira, Cláudia Araújo de (2014)
Increased life expectancy provides the emergence of diseases associated with aging, such as non-communicable chronic diseases, in the population. Due to the relevance of this topic, the aim of this study was to analyze the epidemiological profile of public servants assessed in admission exam for Forensic Medicine Unit of the Integrated Subsystem Attention to the Servant Health of the Federal University of Goiás, from January/2012 to January/2013. It was also established an intervention goal, aiming to develop a proposition of a course of continuing education in health to the public employees of Integrated Subsystem Attention to the Servant Health of the Federal University of Goiás, in order to propose actions for health promotion to those servants of the UFG. It was conducted a retrospective descriptive study of the health conditions of 358 servants hired at UFG, by public tender. The research was conducted through review of medical records and the sample was a convenience (census). The prevalence of overweight, hypertension, hypercholesterolemia, hypertriglyceridemia, smoking and alcohol consumption was respectively: 41.7%, 25,6%, 30.3%, 19.1%, 7.5% and 5.3%. Association was found between body mass index (weight / height ²) with males (p ≤ 0.001) and the levels of blood pressure (p ≤ 0.001). Metabolic syndrome was observed in 19 subjects aged 25-34 years (5,6%), from 339 servants that had at least three associated risk factors. Among the individuals with metabolic syndrome, most have some degree of overweight /obesity with statistical significance amongst individuals with excess of body weight (p ≤ 0.001) and in males (p = 0.002). It was concluded that among examined for admission exam at the Federal University of Goiás, from January 2012 to January 2013, there were: high prevalence of cardiovascular risk factors for the development of non-communicable chronic diseases such as systemic hypertension, hypercholesterolemia, overweight /obesity and metabolic syndrome in a population predominantly composed of young adults, associations between body mass index increased and male sex, systemic hypertension and personal history of hypertension; association between self-reported non-communicable chronic diseases and hypertension; association between metabolic syndrome and male sex and body mass index increased, the low prevalence of self-reported tobacco and alcohol consumption, aptitude in the mental sanity certificate among all the servants; high prevalence of refractive errors in the visual acuity examination and alterations in campimetry; high prevalence of inflammatory onco-parasitic cytology in female servants and low prevalence of altered mammograms; high prevalence of normal electrocardiograms. It’s necessary to intervene with promotional educational activities for UFG servants by actions on health education. Thus, initially it was proposed a course of continuing education to the servants of the Integrated Subsystem Attention to the Server Health of the Federal University of Goiás.